PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DI PERPUSTAKAAN IAIN TULUNGAGUNG - Ema Fatmawati Anindya; Faza Shofa Ainun Nada (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2019)
This study aims to describe the use of information and communication technology at the Tulungagung IAIN Library with various obstacles. The method used is a qualitative research method with a descriptive approach based on empirical data from the results of interviews, data reduction, analysis and conclusion. The technique of collecting data uses observation and interviews. The use of information and communication technology in the current era has spread in almost all aspects of life, including the library. The library is a place to develop information and knowledge managed by educational institutions, as well as educational tools to help facilitate teaching and learning activities of the academic community. The library has a variety of types, one of which is a college library. The college library has a role in supporting the implementation of the Higher Education Tri Dharma, including education, research or research and community service. No wonder this technology is applied in the Library. good service will influence the satisfaction of the user. In this regard the problems encountered at the Tulungagung IAIN Library, such as constraints in network systems and technology, are still not optimally utilized for students in searching online library materials. Therefore, libraries must be able to adapt and develop information and communication technology appropriately into various types of services. Technology-based service activities are expected to be one element that attracts visitors to visit and utilize various sources of information so as to enhance the image of the library